Models for Surrogative Stimulation. - Datteri, Edoardo (Erkenntnis, 2026)
Occasionally, in science, models are used to stimulate other systems rather than to perform surrogative reasoning. More specifically, in what is called surrogative stimulation, a model is used to stimulate a focal system in order to learn how it would respond to the system represented by the model. This article proposes a methodological reconstruction of the surrogative stimulation strategy and addresses the so-called model evaluation problem in relation to it. It is argued that in order to be adequate for surrogative stimulation, the model must provide stimuli that are similar to those provided by the target system, and a tentative definition of 'stimulus similarity' is offered. It is also argued that whether the model and the target system are similar in this sense is a question that depends not only on the context and interests of the modeller, but more crucially on facts about how the focal system works. Representative examples are taken from ethorobotics and social robotics, but the analysis made here is not intended to be applicable only to these areas of research. While much remains to be learned about this emerging use of models, the analysis undertaken here aims to offer a preliminary methodological reconstruction that may be useful for future studies.